Investment Matters : the Role and Patterns of Investment in Southeast Europe. - Handjiski, Borko (World Bank Working Papers, No. 159., 2009)
The purpose of this book is to provide policy insights to decision-makers, academics and researchers on investment flows and patterns in Southeast Europe. The report explores some of the determinants of private investment, such as: the financing sources for investment, the contribution of FDI and the role of public investment. It finds that investment rates in SEE are substantially lower than among the EU-8 and the fast growing East Asian economies, which could explain partly the slower economic growth in SEE.